Eros and Astrology in the Περίοδοι Πέτρου: The Sense of the Pseudo-Clementine Novel - Jones, F. Stanley (Apocrypha, 2001)
This article presents the only ancient Christian novel that has survived, the Pseudo-Clementines. It reviews previous scholarship and argues that the topic of astrology is the key to both the structure of the novel and its title.